Redox Denaturation of Proteins: Electrochemical Treatment of Egg Plasma. Issue 12 (7th August 2019) - Taniguchi, Daisuke; Handa, Akihiro; Kodama, Risa; Okada, Yohei; Chiba, Kazuhiro
Abstract: Although acid/base reactions are used widely to denature proteins during food processing, the application of reduction/oxidation (redox) reactions are relatively rare in this field. Herein, we demonstrate a "redox denaturation" of proteins, using egg plasma as a model. Electrochemical treatment of egg plasma in the presence of iodide ion (I − ) selectively induced intramolecular disulfide bond formations, resulting in a different type of denaturation than that achieved via heat treatment. The reaction mechanism was examined through electrochemical analysis using cyclic voltammetry. Although the involvement of hypervalent iodine ("I + ") cannot be ruled out, molecular iodine (I2 ) generated at the surface of anode is the most likely oxidizing agent that formed the disulfide bonds. We believe that the redox denaturation of proteins described herein would be a promising approach in food processing and can find practical applications in this field. Abstract : A "redox denaturation" of proteins has been demonstrated using egg plasma as a model. Electrochemical treatment of egg plasma in the presence of iodide ion (I − ) selectively induced intramolecular disulfide bond formations, resulting in a different type of denaturation than that achieved via heat treatment. The reaction mechanism was examined through electrochemical analysis using cyclic voltammetry.